2004
DOI: 10.1016/j.jom.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

TQM across multiple countries:Convergence HypothesisversusNational Specificityarguments

Abstract: We provide conceptual clarity and new empirical findings for the question of whether or not TQM is universal in its applicability. At the conceptual level, we reposition and reframe the ''universality of TQM'' question in light of two conflicting theoretical perspectives in the international business literature -one that supports the universal applicability of TQM (i.e., the Convergence Hypothesis argument) and another that questions the universal applicability of TQM (i.e., the National Specificity argument).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 83 publications
(95 reference statements)
8
128
1
2
Order By: Relevance
“…The authors reported that these control practices were similar across MNCs, indicating that they converged due to normative and mimetic pressures as suggested by institutional theory. Rungtusanatham et al (2005) also found evidence for the convergence hypothesis by comparing Deming management principles across companies located in several different countries. This study also takes the position that US companies and foreign companies operating in the US will mimic each other's TQM practices and create similar structures to look legitimate to important stakeholders.…”
Section: Country Of Originmentioning
confidence: 88%
“…The authors reported that these control practices were similar across MNCs, indicating that they converged due to normative and mimetic pressures as suggested by institutional theory. Rungtusanatham et al (2005) also found evidence for the convergence hypothesis by comparing Deming management principles across companies located in several different countries. This study also takes the position that US companies and foreign companies operating in the US will mimic each other's TQM practices and create similar structures to look legitimate to important stakeholders.…”
Section: Country Of Originmentioning
confidence: 88%
“…These similar findings could be used for TQM adoption across different cultures. However, minor differences were detected, and therefore the implementation of certain TQM practices vary, as suggested by several scholars (Solis et al, 2000;Rungtusanatham et al, 2005). Nevertheless, it may also happen that certain TQM practices can follow indistinguishable patterns in country-to-country comparisons; for instance, between Japan and the USA (Rungtusanatham et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the adoption of a contingent focus for QM is increasingly assumed in the literature, as it enables to justify that the performance obtained depends on variables in the internal and external context (e.g., Adam & Foster, 2000;Das, Handfield, Calantone, & Ghosh, 2000;Douglas & Judge, 2001;Melan, 1998;Reed, Lemak, & Montgomery, 1996;Sitkin, Sutcliffe, & Schroeder, 1994;Roca-Puig, Escrig-Tena, Bou-Llusar, & Beltrán-Martín, 2006;Sila, 2007;Sousa, 2003;Sousa & Voss, 2001). The contextual factors most frequently considered have been the size of the organization, the kind of activity it performs (manufacturing or services), the number of years of implementation, ISO 9000 registration and the country of origin (e.g., Martínez-Lorente, Gallego-Rodríguez, & Dale, 1998;Roca-Puig et al, 2006;Rungtusanatham, Forza, Koka, Salvador, & Nie, 2005;Sharma, 2006;Sila, 2007;Solis, Raghunathan, & Rao, 2000). Notably, very little research has been devoted to understanding quality practices in different industrial contexts and linking them to implementation efforts and quality outcomes (Chong & Rundus, 2004;Das et al, 2000;Rungtusanatham et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The contextual factors most frequently considered have been the size of the organization, the kind of activity it performs (manufacturing or services), the number of years of implementation, ISO 9000 registration and the country of origin (e.g., Martínez-Lorente, Gallego-Rodríguez, & Dale, 1998;Roca-Puig et al, 2006;Rungtusanatham, Forza, Koka, Salvador, & Nie, 2005;Sharma, 2006;Sila, 2007;Solis, Raghunathan, & Rao, 2000). Notably, very little research has been devoted to understanding quality practices in different industrial contexts and linking them to implementation efforts and quality outcomes (Chong & Rundus, 2004;Das et al, 2000;Rungtusanatham et al, 2005).…”
Section: Introductionmentioning
confidence: 99%